Mineral Chemistry and Iron Isotope Characteristics of Magnetites in Pertek Fe-Skarn Deposit (Türkiye) - Kara, Hatice; Yalcin, Cihan; Erturk, Mehmet Ali; Kalender, Leyla (Mdpi, 2025)
This study investigates the mineral chemistry and iron isotope composition of the Pertek Fe-skarn deposit in the Eastern Taurides, Turkey, to elucidate skarn formation and ore genesis through chemical and isotopic parameters. The deposit consists of substantial and dispersed magnetite ores formed by the intrusion of a dioritic suite into marbles. Mineral assemblages, including hematite, goethite, andradite garnet, hedenbergite pyroxene, calcite, and quartz, exhibit compositional variations at different depths within the ore body. Magnetite is commonly associated with hematite, goethite, garnet, pyroxene, calcite, and quartz. Extensive LA-ICP-MS analysis of magnetite chemistry reveals elevated trace element concentrations of titanium (Ti), aluminum (Al), vanadium (V), and magnesium (Mg), distinguishing Pertek magnetite from low-temperature hydrothermal deposits. The enrichment of Ti (>300 ppm) and V (>200 ppm), along with the presence of Al and Mg, suggests formation from high-temperature hydrothermal fluids exceeding 300 degrees C. Discriminant diagrams, such as Al+Mn versus Ti+V, classify Pertek magnetite within the skarn deposit domain, affirming its medium- to high-temperature hydrothermal origin (200-500 degrees C), characteristic of skarn-type deposits. Magnetite thermometry calculations yield an average formation temperature of 414.53 degrees C. Geochemical classification diagrams, including Ni/(Cr+Mn) versus Ti+V and TiO2-Al2O3-MgO+MnO, further support the skarn-type genesis of the deposit, distinguishing Pertek magnetite from other iron oxide deposits. The Fe-skarn ore samples display low total REE concentrations, variable Eu anomalies, enrichment in LREEs, and depletion in HREEs, consistent with fluid-rock interactions in a magmatic-hydrothermal system. The delta Fe-56 values of magnetite range from 0.272 parts per thousand to 0.361 parts per thousand, while the calculated delta Fe-56_aq values (0.479 parts per thousand to 0.568 parts per thousand) suggest a magmatic-hydrothermal origin. The delta Fe-57 values (0.419 parts per thousand to 0.530 parts per thousand) and the calculated 10(3)ln beta value of 0.006397 indicate re-equilibration of the magmatic-hydrothermal fluid during ore formation.
Keywords: Tethyan region; Fe-skarn; Fe isotopes; magnetite chemistry; T & uuml;rkiye